Patients' experiences of care and support at home after a family member's participation in an intervention during palliative care. Issue 3 (17th October 2016) - Norinder, Maria; Goliath, Ida; Alvariza, Anette
ABSTRACT: Objective: Patients who receive palliative home care are in need of support from family members, who take on great responsibility related to caregiving but who often feel unprepared for this task. Increasing numbers of interventions aimed at supporting family members in palliative care have been described and evaluated. It is not known whether and how these interventions actually affect the care or support provided to a patient, even though it has been suggested that family members would be likely to provide better care and support and thus allow for positive experiences for patients. However, this has not been studied from the perspective of the patients themselves. The objective of our study was to explore patients' experiences of care and support at home after family members' participation in a psychoeducational intervention during palliative care. Method: Our study took a qualitative approach, and interviews were conducted with 11 patients whose family members had participated in a psychoeducational intervention during palliative home care. The interviews were analyzed employing interpretive description. Results: Patients' experiences were represented by three themes: "safe at home, " "facilitated and more honest communication, " and "feeling like a unit of care." Patients felt that their needs were better met and that family members became more confident at home without risking their own health. Patients felt relieved when family members were given the opportunity to talk and reflect with others and hoped that the intervention would contribute to more honest communications between themselves and their family members. Further, it was of great importance to patients that family members receive attention from and be confirmed and supported by healthcare professionals. Significance of results: Our findings show how an intervention targeted at family members during palliative home care also benefits the patients.